Identifikasi Lapisan Batubara Pada Batuan Sedimen Pre-Tersier Menggunakan Metode Wireline Logging Untuk Potensi Coalbed Methane (CBM) Pada Sumur AB Lapangan X - Eko Prastio; Abdullah Rizky Agusman; Nur Fikriyah Mutmainah (Fakultas Teknik Universitas Bhayangkara Jakarta Raya, 2022)
Wireline Logging is the activity of collecting and recording data on physical parameters according to the depth of the borehole during the drilling process. The measured data are radioactivity, speed of sound and electromagnetic. Methane gas trapped in coal or commonly referred to as Coalbed Methane is one of the alternative energy sources where the existing conventional gas has decreased production and no other new gas fields have been found. The Muara Enim Formation, which is the main target of mining companies, contains abundant brown coal or lignite from the South Sumatra region. The existing log data will be interpreted and evaluated qualitatively and identified the presence of the coal seam using wireline logging. Coalbed methane or CBM is an alternative energy source that can be utilized. The gas trapped in the coal seam will be utilized, because this research will identify the coal seam by using a wireline logging tool in well AB field X. Through the interpretation of logging results using gamma ray log data and density log data from several zones in the same location . Gamma ray log data and density logs will detect coal seams because there is a radioactive element in the coal, namely potassium. With a low gamma ray log value and a low density log value, it will be possible to have a coal seam in well AB field X.